2024
DOI: 10.3390/cancers16061108
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Burden of Psychiatric Cancer Patients: A Narrative Review

Gniewko Więckiewicz,
Sophie Weber,
Iga Florczyk
et al.

Abstract: This comprehensive review article examines the complex overlap of affective disorders, psychoses, addictions, anxieties, post-traumatic stress disorder, and somatic symptom disorder in the context of cancer patients, and highlights the intricate interplay between psychiatric and oncological diagnoses. Based on extensive literature, it highlights the profound socioeconomic burdens that result from the coexistence of these disorders. The analysis includes the increased healthcare costs, impaired adherence to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…In recent years, there has been a growing recognition of the importance of addressing the psychosocial aspects of cancer care (Grassi et al, 2017) [9] . Research has highlighted the profound impact of cancer on mental health, relationships, and overall quality of life (Więckiewicz et al, 2024) [29] . Moreover, studies have shown that psychosocial support can significantly improve patient outcomes, including treatment adherence, coping abilities, and emotional well-being (Smith et al, 2021) [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a growing recognition of the importance of addressing the psychosocial aspects of cancer care (Grassi et al, 2017) [9] . Research has highlighted the profound impact of cancer on mental health, relationships, and overall quality of life (Więckiewicz et al, 2024) [29] . Moreover, studies have shown that psychosocial support can significantly improve patient outcomes, including treatment adherence, coping abilities, and emotional well-being (Smith et al, 2021) [23] .…”
Section: Introductionmentioning
confidence: 99%